TACE plus lenvatinib and tislelizumab for intermediate-stage hepatocellular carcinoma beyond up-to-11 criteria: a multicenter cohort study - Chen, Song; Shuangyan, Tang; Shi, Feng; Cai, Hongjie; Wu, Zhiqiang; Wang, Liguang; Ma, Ping; Zhou, Yuanmin; Mai, Qicong; Wang, Fan; Lai, Jiaming; Chen, Xiaoming; et al. (Frontiers in Immunology, 2024)
Background: Intermediate-stage (BCLC-B) hepatocellular carcinoma (HCC) beyond the up-to-11 criteria represent a significant therapeutic challenge due to high and heterogeneous tumor burden. This study evaluated the effectiveness and safety of transarterial chemoembolization (TACE) in combination with lenvatinib and tislelizumab for these patients.In this retrospective cohort study, patients with unresectable intermediate-stage HCC beyond the up-to-11 criteria were enrolled and divided into TACE monotherapy (T), TACE combined with lenvatinib (TL), or TACE plus lenvatinib and tislelizumab (TLT) group based on the first-line treatment, respectively. The primary endpoint was overall survival (OS). The secondary outcomes included progression-free survival (PFS), tumor response according to RESIST1.1 and modified RECIST, and adverse events (AEs).Overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and treatment-related adverse events (TRAEs) were recorded and analyzed.Results: There were 38, 45, and 66 patients in the T, TL, and TLT groups, respectively. The TLT group exhibited significantly higher ORR and DCR than the other two groups, as assessed by either mRECIST or RECIST 1.1 (all P<0.05). Median PFS and OS were significantly longer in the TLT group compared with the T group (PFS: 8.5 vs. 4.4 months; OS: 31.5 vs. 18.5 months; all P<0.001) and TL group (PFS: 8.5 vs. 5.5 months; OS: 31.5 vs. 20.5 months; all P<0.05). The incidence of TRAEs was slightly higher in the TLT and TL groups than in the T group, while all the toxicities were tolerable. No treatment-related death occurred in all groups.Conclusions: TACE combined with lenvatinib and tislelizumab significantly improved the survival benefit compared with TACE monotherapy and TACE plus lenvatinib in patients with intermediate-stage HCC beyond the up-to-11 criteria, with an acceptable safety profile.